The Influence of AI Ethics in HR and Algorithm Transparency on Employee Trust in the Manufacturing Industry - Supiah Ningsih; Danil Syahputra; Nazifah Husainah; Adityo Ari Wibowo; Cikita Berlian Hakim (West Science Social and Humanities Studies, 2026)
This study examines the influence of artificial intelligence (AI) ethics in human resources and algorithm transparency on employee trust in the manufacturing industry. The rapid adoption of AI in organizational management has transformed HR practices, including recruitment, performance evaluation, and workforce management, by enabling more efficient and data-driven decision-making. However, the use of AI also raises concerns regarding ethical governance and the transparency of algorithmic decision-making processes. This research employs a quantitative approach using a survey method involving 150 employees working in manufacturing companies. Data were collected through structured questionnaires measured on a five-point Likert scale and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS 3). The results indicate that AI ethics in HR has a positive and significant effect on employee trust, suggesting that the application of ethical principles in AI-based HR practices enhances employees’ perceptions of fairness and organizational responsibility. In addition, algorithm transparency also shows a positive and significant influence on employee trust, demonstrating that clear explanations of AI decision-making processes can increase employees’ confidence in technology-driven HR systems. The structural model reveals that both variables explain 63% of the variance in employee trust (R² = 0.63). Overall, these findings emphasize the importance of responsible AI governance and transparent algorithmic systems in strengthening employee trust and supporting the sustainable adoption of AI technologies within organizations.